2020
DOI: 10.3390/ijerph17165859
|View full text |Cite
|
Sign up to set email alerts
|

Placing Greater Torque at Shorter or Longer Muscle Lengths? Effects of Cable vs. Barbell Preacher Curl Training on Muscular Strength and Hypertrophy in Young Adults

Abstract: Muscular strength and hypertrophy following resistance training may be obtained in different degrees depending on the approach performed. This study was designed to compare the responses of the biceps brachii to two preacher curl exercises, one performed on a cable-pulley system (CAB; in which a greater torque was applied during the exercise when elbows were flexed and biceps shortened) and one performed with a barbell (BAR; in which greater torque was applied when the elbows were extended and biceps stretched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Training intensity was increased progressively from 30% (1st session) to 50% (2nd and 3rd sessions), 70% (4th and 5th sessions), 80% (6th and 7th sessions), 90% (8th and 9th sessions), and 100% (10th session) of the MVC-ISO torque at 50° for the EXT, and at 90° for the FLE group measured before the training. The dominant arm of each participant was positioned on a preacher curl bench in a seated position, with 45° shoulder flexion and forearm supination ( Nunes et al, 2020 ). Each session consisted of 3 sets of 10 repetitions (30 repetitions in total).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training intensity was increased progressively from 30% (1st session) to 50% (2nd and 3rd sessions), 70% (4th and 5th sessions), 80% (6th and 7th sessions), 90% (8th and 9th sessions), and 100% (10th session) of the MVC-ISO torque at 50° for the EXT, and at 90° for the FLE group measured before the training. The dominant arm of each participant was positioned on a preacher curl bench in a seated position, with 45° shoulder flexion and forearm supination ( Nunes et al, 2020 ). Each session consisted of 3 sets of 10 repetitions (30 repetitions in total).…”
Section: Methodsmentioning
confidence: 99%
“…They showed that maximal voluntary concentric contraction torque (12–13%) and knee extensor muscle volume (4.8–8.2%) increased significantly only after the longer muscle length training. In a dynamic resistance exercise study, Nunes et al (2020) compared two types of bicep curl training with a cable-pulley system which induced greater torque at short muscle lengths vs. a barbell which could apply greater torque at long muscle lengths, performed three times a week for 10 weeks for changes in muscle strength and thickness of the elbow flexors. They showed that maximum voluntary isometric contraction (MVC-ISO) strength at a long muscle length (20° elbow flexion) increased significantly greater after the barbell (39%) than the cable-pulley training (30%) without a difference in biceps brachii thickness increase.…”
Section: Introductionmentioning
confidence: 99%
“…Among the exercises performed with intent to stimulate the upper limb muscles, the biceps curl is definitely one of the most common. Basically, a biceps curl consists of an elbow flexion against an external resistance that, when constant, can be a dumbbell, a barbell, a cable or a selectorized load on a gym device [ 10 , 11 , 12 , 13 , 14 , 15 ]. The biceps curl has its main target in the elbow flexors, i.e., brachialis, brachioradialis and biceps brachii.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, between-exercise variables may still be listed, as for example the type of load (e.g. cables, elastic bands, barbells/dumbbells, isoinertial devices) that appear to lead to different short-term or long-term strength and structural adaptations [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%